Anomalous behaviour of X-ray absorption observed on the highly correlated cerium nitride (CeN) compound - Kappler, J.P. (1991)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Université de Nancy; Francia